Analysis of a Mid Rise Structure Considering Floating Column with different Arrangements of Beams below using Staad.Pro : A Review - Awaneesh Nema; Vedant Shrivastava (International Journal of Scientific Research in Civil Engineering, 2021)
Floating columns are one of the important aspects of multi-storey structures due to their various advantages thus seem to be unavoidable. Floating columns are generally not found reliable in seismic prone areas. This research is followed towards analyzing the performance of floating columns structure considering different beam arrangements prone to seismic load. In this paper we are presenting review of literatures related analysis of floating column structures using analysis tools and lateral load conditions.